2012
DOI: 10.7314/apjcp.2012.13.5.1737
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Migration Inhibitory Factor: a Potential Marker for Cancer Diagnosis and Therapy

Abstract: Macrophage migration inhibitory factor (MIF) is a pluripotent cytokine which plays roles in inflammation, immune responses and cancer development. It assists macrophages in carrying out functions like phagocytosis, adherence and motility. Of late, MIF is implicated in almost all stages of neoplasia and expression is a feature of most types of cancer. The presence of MIF in almost all tumors and all stages of cancer makes it an interesting candidate for cancer therapy. This review explores the roles of MIF in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 96 publications
1
35
0
1
Order By: Relevance
“…Chronic inflammation plays an important role in various aspects of cancer involving cancer initiation, promotion, progression, metastasis and clinical features (Balkwill et al, 2001;Mantovani et al, 2008;Babu et al, 2012) which has gradually attracted the attention of relevant researchers worldwide due to the rising incidence of cancer in public. Cancer-related inflammation has been recognized as the seventh hallmark of cancer (Colotta et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic inflammation plays an important role in various aspects of cancer involving cancer initiation, promotion, progression, metastasis and clinical features (Balkwill et al, 2001;Mantovani et al, 2008;Babu et al, 2012) which has gradually attracted the attention of relevant researchers worldwide due to the rising incidence of cancer in public. Cancer-related inflammation has been recognized as the seventh hallmark of cancer (Colotta et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The source of CXCL12 in the liver is still not entirely clear but recent studies identified HSEC, Kupffer cells (59), and activated HSC (60) as potential producers of this chemokine. Another CXCR4-interacting cytokine is the macrophage migration inhibitory factor (MIF) that has been implicated in various stages of cancer progression (61) and recently identified as a potential marker for CRC liver metastasis (62). CCL20/CCR6 were also implicated in CRC liver metastases, based on a strong association between the CCR6 staining intensity in primary CRC specimens and the development of synchronous liver metastases (63).…”
Section: Chemokine/chemokine Receptors Recruit Circulating Tumor and mentioning
confidence: 99%
“…Systemic inflammatory response (SIR) is an important prognostic factor for survival in various types of cancer (5,6). Neutrophils, platelets, lymphocytes and albumin play a prominent role in cancer-related inflammation.…”
Section: Introductionmentioning
confidence: 99%